2016
DOI: 10.1590/0037-8682-0159-2015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypovitaminosis D and its association with oral lesions in HIV-infected Brazilian adults

Abstract: Introduction:This study assessed the prevalence of hypovitaminosis D and its association with oral candidiasis and clinical parameters of periodontitis (CPP) in HIV-infected patients. Methods: Periodontal examinations for the 113 HIV-infected patients were recorded using the Community Periodontal Index. A cytological smear from the lateral borders of the tongue was performed to evaluate candidiasis. Results: The frequency of hypovitaminosis D was 23.9%. In multivariate analysis, only the duration of exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Another study evaluated an Indonesian population and found that 25(OH)D levels were not correlated with ABL . A study conducted in HIV‐infected Brazilian adults that analyzed the correlation of 25(OH) levels with Community Periodontal Index criteria also did not find significant associations …”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Another study evaluated an Indonesian population and found that 25(OH)D levels were not correlated with ABL . A study conducted in HIV‐infected Brazilian adults that analyzed the correlation of 25(OH) levels with Community Periodontal Index criteria also did not find significant associations …”
Section: Resultsmentioning
confidence: 96%
“…Ten studies evaluated samples from the general population, 3 studies included only older men, 4 studies assessed exclusively post‐menopausal women and 2 included older women . Other studies evaluated patients with specific health conditions (pregnant women, hospital patients, breast cancer survivors, HIV‐infected adults, liver transplant patients) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations